The Interplay of Organizational Support, Performance Management, and Work-life Management on Employee Retention in Islamic Retail - Saputra, Megi; Rahmawaty, Penny (Suhuf: International Journal of Islamic Studies, 2026)
Background: The Indonesian retail sector exhibits robust macroeconomic growth, yet organizations face severe internal destabilization driven by high turnover and "quiet quitting" among Generation Z and Millennial frontline workers. Objective: This study aims to systematically investigate the structural and psychological mechanisms driving retention by analyzing the effects of Perceived Organizational Support (POS), Performance Management, and Work-Life Balance (WLB), while evaluating the mediating role of Organizational Commitment and the moderating boundary condition of Supervisor Support. Methodology: A quantitative, cross-sectional explanatory survey was conducted using saturated census sampling on 175 operational employees at Pamella Supermarket Yogyakarta. Data were analyzed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. Results: The structural model demonstrates that WLB is the sole independent variable directly and significantly driving both retention and organizational commitment. POS and Performance Management failed to influence retention directly. However, Supervisor Support significantly moderated and activated the effect of POS on retention. Organizational Commitment strongly mediated the WLB-retention pathway. Conclusion: Work-life balance is the paramount determinant of retention for modern retail workers. Systemic organizational support remains inert unless translated through the empathetic, interpersonal engagement of immediate supervisors.